Dynamic analysis of expression of chemokine and cytokine gene responses to H5N1 and H9N2 avian influenza viruses in DF‐1 cells. (4th May 2018) - Luo, Chang; Liu, Jianxin; Qi, Wenbao; Ren, Xujiao; Lu, Rong; Liao, Ming; Ning, Zhangyong
ABSTRACT: H5N1 and H9N2 are the most important causes of avian influenza in China. Chemokines and cytokines play important roles in inflammatory response that clearly differ between H5N1 and H9N2 infection. To investigate whether chemokines and cytokines are differentially regulated following H5N1 and H9N2 AIVs infection, dynamic expression of chemokines and cytokines, including IL8L1, IL8L2, CX3CL1, CCL5, CCL20, K203, SCYA4, XLC1, CCLi10, CCL19, IFN‐α, IFN‐β, IL‐1β, IL‐6 and TNF‐α, were analyzed by real‐time quantitative RT‐PCR in DF‐1 cells. It was found that IL8L1, IL8L2, CX3CL1, CCL5, CCL20, K203, SCYA4, IFN‐α, IFN‐β, IL‐1β, IL‐6 and TNF‐α increased significantly after induction of H5N1 or H9N2 AIV infection, whereas no expression of XCL1, CCLi10 or CCL19 was detected. H9N2 AIV infection was associated with much stronger chemokine responses than infection with H5N1, whereas the cytokines showed opposite results. It was found that K203 is a constant chemotactic factor independent of subtype of AIVs and infectious dose, CCL20 and IL‐1β are constant regardless of the infectious dose but depend on the subtype of AIV, chemotactic factors IL8L1, IL8L2 and CCL5 are dependent both on subtype of AIVs and infectious dose, and K203, CX3CL1, SCYA4, CCL20, IFN‐α, IL‐1β and TNF‐α are specific to responses to H5N1 AIV infection whereas K203, CCL20, IFN‐β, IL‐1β and IL‐6 are specific to H9N2 infection. These results provide basic data for explaining differences in inflammation and phenotypes of histopathological changes caused by H5N1 and H9N2 and add new information on the roles of chemokines and cytokines in virulence of AIVs.